Pengaruh Penilaian Kinerja Dan Komitmen Terhadap Produktivitas Kerja Perawat Di Rumah Sakit Umum Sakina Idaman Sleman Yogyakarta - Ary Subiyantoro, SE, MM (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2022)
This writing aims to determine how the influence of performance appraisal and commitment to the work productivity of nurses at Sakina Idaman General Hospital, Sleman Yogyakarta. The data analysis technique uses valid data testing, reliable data, multiple regression analysis, f test and t test. Based on the results of the study, the results of the multiple regression equation Y = 14.956 + 0.401X1 + 0.253X2, indicating that there is an effect of performance appraisal and commitment on work productivity. From the results of the coefficient of determination test, it shows that R Square is 0.241. This means that the magnitude of the influence of the performance appraisal variable and commitment on the work productivity of nurses at Sakina Idaman General Hospital is 24.1%, the remaining 75.9% is explained by other causal factors.